2021
DOI: 10.1007/s00345-021-03628-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of De Ritis ratio in metastatic renal cell carcinoma treated with tyrosine-kinase inhibitors

Abstract: Background Predictive markers can help tailor treatment to the individual in metastatic renal cell carcinoma (mRCC). De Ritis ratio (DRR) is associated with oncologic outcomes in various solid tumors. Objective To assess the value of DRR in prognosticating survival in mRCC patients treated with tyrosine-kinase inhibitors (TKI). Methods Overall, 220 mRCC patients treated with TKI first-line therapy were analyzed. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…However, it is difficult to select Currently, drug treatments for metastatic RCC are diverse and stratified by risk factors using models such as those from the Memorial Sloan-Kettering Cancer Center and the International Metastatic RCC Database Consortium. However, it is difficult to select appropriate cases for study [8][9][10][11][12][13][14][15][16]. In addition, the effectiveness of therapeutic agents has been investigated primarily using nuclear gene information.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to select Currently, drug treatments for metastatic RCC are diverse and stratified by risk factors using models such as those from the Memorial Sloan-Kettering Cancer Center and the International Metastatic RCC Database Consortium. However, it is difficult to select appropriate cases for study [8][9][10][11][12][13][14][15][16]. In addition, the effectiveness of therapeutic agents has been investigated primarily using nuclear gene information.…”
Section: Introductionmentioning
confidence: 99%
“…A problem of the study by Su is their interpretation of OS since the data provided by the original research in their studies all indicated that an elevated De Ritis ratio had poor survival. Furthermore, a recent study reported that the De Ritis ratio was not associated with RCC prognosis (31). Thus, it is necessary to reevaluate the role of the De Ritis ratio in the prognosis of RCC based on the existing literature to better guide clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…After full-text evaluation, 12 studies were excluded from the remaining 25 potential studies, including 6 without survival outcomes, 3 without adequate survival data, and 5 without De Ritis ratio data. Finally, eleven articles comprising 6,258 patients were included in the present analysis (18,19,(23)(24)(25)(26)(27)(28)(29)(30)(31) (Figure 1). Table 1 records the basic characteristics of all included studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations